Long-term serial changes of cardiac sympathetic nerve dysfunction in acute decompensated heart failure patients with reduced, mid-range and preserved left ventricular ejection fraction. (25th November 2020) - Seo, M; Yamada, T; Watanabe, T; Morita, T; Furukawa, Y; Tamaki, S; Kawasaki, M; Kikuchi, A; Kawai, T; Fukunami, M
Abstract: Background: Cardiac sympathetic nerve dysfunction, which is assessed by I-123 metaiodobenzylguanidine (MIBG) imaging, is associated with the poor outcomes in patients with chronic heart failure (CHF). Serial evaluation of cardiac MIBG imaging was shown to be useful for predicting adverse outcome in CHF. However, there was no information available on long-term serial changes of cardiac sympathetic nerve dysfunction after discharge of acute decompensated heart failure (ADHF) hospitalization. Purpose: We aimed to clarify the serial change of cardiac MIBG imaging parameter in long-term after discharge of heart failure hospitalization, especially relating to HFrEF (LVEF<40%), HFmrEF (40%≤LVEF<50%) and HFpEF (LVEF≥50%). Methods: We studied 112 patients (HFrEF; n=44, HFmrEF; n=23 and HFpEF; n=45) who were admitted for ADHF, discharged with survival and without heart failure hospitalization during follow-up period. All patients underwent cardiac MIBG imaging at the timing of discharge, in 6–12 months and in 18–24 months after discharge. The cardiac MIBG heart to mediastinum ratio (H/M) was calculated on the early image and the delayed image (late H/M). The cardiac MIBG washout rate (WR) was calculated from the early and delayed planar images after taking radioactive decay of I-123 into consideration. Results: In HFrEF patients, late H/M was significantly improved from discharge to 6–12 months data (1.60±0.24 vs 1.75±0.31, p<0.0001). Late H/M of HFmrEF patients was also significantly improved from discharge to 18–24 months data (1.71±0.27 vs 1.84±0.29 p=0.043). On the other hand, late H/M of HFpEF patients was not significantly changed. As for WR, WR in HFrEF and HFmrEF patients was significantly improved from discharge to 18–24 months data, although WR of HFpEF was not significantly changed. Conclusion: The improvement in cardiac sympathetic nerve dysfunction was observed in patients with HFrEF and HFmrEF, not in HFpEF, after the discharge of acute heart failure hospitalization. Funding Acknowledgement: Type of funding source: None